Severity and mortality of critically ill patients on invasive mechanical ventilation (Research, Society and Development, 2022)
Objective: to evaluate the severity and mortality of critically ill patients on invasive mechanical ventilation (IMV). Method: cohort developed between January 2020 and July 2021 with 53 patients on mechanical ventilatory support admitted to intensive care. A structured questionnaire with closed questions was used to collect data obtained from the patient's electronic medical record. Chi-square, Fisher Exact, Mann-Whitney and Wilcoxon signed Rank Sum tests were used for statistical analysis. Results with p≤0.05 were significant. Research project approved by the Ethics Committee under CAAE:87170218.9.0000.0030. Results: acute kidney injury (AKI) affected 98.1% of patients on mechanical ventilation. Most patients evolved with KDIGO 3 (69.8%). Older patients had a higher risk of death [OR 4.4 (95% CI 1.4-14.3), p = 0.01]. Conclusion: Most patients on IMV evolved with more severe AKI (KDIGO 3) and with a poor prognosis, which resulted in a higher risk of death for elderly patients.